Analisis Pemindahan Material Secara Manual Pada Pekerja Dengan Menggunakan Metode Rapid Entire Body Assessment - Petrus Saut Parulian Simbolon; Sri Zetli (LPPM Universitas Putera Batam, 2020)
PT Glory Propertindo, still manually moving material. Manual material removal is usually done by lifting, carrying, and laying. The activity raises several complaints from construction workers. The purpose of this study was to investigate the perceived grievances of manual material removal workers and to analyze the extent of injury risk based on the rapid overall body assessment (REBA) method. data were collected by using nordic body map questionnaires to 8 bronze and cement carrier workers and then analyzing the level of risk of injury on postural work assessment using Rapid Total Body Assessment (REBA) method. For the results showed the body parts that got the pain and the pain in the left and right shoulder, left and right upper arm, back, waist and lower waist, buttocks, left elbow and right elbow, left and right arm, left arm wrist And right, left and right hands, left and right thighs, left and right legs, left and right legs and potential diseases that occur are discoloration,kyphosis, lower back pain, bursitis, neck stiffness, cramps, and sprains. The result of the appraisal shows that the activity of laying concrete and cement has a very high risk, so it is necessary to take corrective action now